PROTOIPE SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT GIGI DAN MULUT - Ade Chandra Saputra (Universitas Palangka Raya, 2015)
Reluctance and fear of society in dental treatment can cause diseases that attack the body's other organs. Research through the creation of expert systems that can help users to deal with complaints of dental and oral diseases can be applied to address the above problems. The research followed by tests on 20 people with gum disease to test the accuracy of the system and display interface system based on subjective assessment. The test results of 20 patients will be analyzed again by the expert to prove the accuracy of the rules used in the system.Less precise method of forward chaining expert system implemented in the case of diagnosis, because more doctors reasoning leads to the backward chaining. However, in its implementation forward chaining method can be applied in this system well based on expert analysis with probability 0.9 accuracy, the accuracy of the diagnosis by the doctor to the user similarity of 0.8, as well as a subjective assessment by the average user 8.03125.